Menimbang Kualitas Pendidikan Islam Dan Kompmpetensi Manajerial Kepala S Sekolah - Een Solihah (Mukaddimah: Jurnal Studi Islam, 2018)
The issue of Islamic education until now still questioned its success. This is reinforced by the argument with the number of student delinquency. The act of disturbing and bullying friends at the schoolmate and so forth. In extreme Islamic education which is based on the formation aklaqul karimah still fail even though this is not absolute. Application of manners derived from the teachings of religion, seemed still giddy and absurd. Therefore, there needs to be a new construction of Islamic education that is associated with religious teaching and practice in everyday life. However, the quality of Islamic education eventually ran to the competence of its managers. In the sense that the leadership of the institution becomes an important role because in hand it is an institution will look dynamic. In the hands of managers or leaders with managerial skills will be able to influence an Islamic educational institution. Great hope from stakeholders that Islamic educational institutions produce smart and true students will become a reality.